2015
DOI: 10.1111/ijcp.12600
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of eye healthcare professionals in the assessment of glaucoma - a systematic review

Abstract: The studies included in this review show promising results, including those raters without ophthalmology training. A lack of power calculations, unequal sample sizes in some studies and the diversity of the testing procedures used make it difficult to make sound inferences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Even after training, nonexpert ophthalmologists demonstrated interobserver agreement of 0.27 [10]. Although definitions of nonexperienced clinicians/evaluators varied among studies, glaucoma experts always showed better interobserver agreement [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Even after training, nonexpert ophthalmologists demonstrated interobserver agreement of 0.27 [10]. Although definitions of nonexperienced clinicians/evaluators varied among studies, glaucoma experts always showed better interobserver agreement [21]. …”
Section: Discussionmentioning
confidence: 99%
“…Karimi et al, [23] indicate that the country has an inadequate number of technicians that is necessary to help in Kenya achieving the middle-income economic status through the manufacturing sector. This means that there is uncertainty in the future of these growth projections despite the major investments in infrastructural projects that cannot be well facilitated since as noted by the vision 2030 blueprint, there is still an existing shortfall the supply of technicians.…”
Section: Tvet Curriculum Development In Kenyamentioning
confidence: 99%